2017
DOI: 10.1016/j.jvs.2016.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Maximal aortic diameter affects outcome after endovascular repair of abdominal aortic aneurysms

Abstract: Maximal aortic diameter is associated with long-term outcomes after elective EVAR. Patients with large AAAs (≥6.0 cm) have higher all-cause mortality, complication, and reintervention rates after EVAR than those with smaller aneurysms. We continue to recommend that AAAs be repaired when they reach 5.5 cm as recommended by the guidelines of the Society for Vascular Surgery. On the basis of our data, EVAR should be considered even in high-risk patients with a maximal aortic diameter between 5.5 and 6.0 cm becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
(56 reference statements)
1
17
1
1
Order By: Relevance
“…Like other studies, 19 we found that large aneurysms (>75 mm) were a highly independent predictor of late all-cause mortality, regardless of AAA complexity. Likewise, chronic baseline renal insufficiency (estimated glomerular filtration rate of <60) was found to also be a significant predictor of late all-cause mortality in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Like other studies, 19 we found that large aneurysms (>75 mm) were a highly independent predictor of late all-cause mortality, regardless of AAA complexity. Likewise, chronic baseline renal insufficiency (estimated glomerular filtration rate of <60) was found to also be a significant predictor of late all-cause mortality in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Previous analyses investigating size effect reported that AAA size ≥6 cm is associated with increased long-term mortality. 11,13 In an unbiased approach to identify a cutoff for AAA size, receiver operating curve (ROC) analysis was first conducted to explore whether there was an optimal cut point of AAA size that increased morality risk. Outcomes included in this study were 3-and 5-year (mid-term) all-cause mortality and 10-year (long-term) allcause mortality.…”
Section: Definitions and Endpointsmentioning
confidence: 99%
“…14 Results from the PIVOTAL and CAESAR randomised trials confirm no benefit in treating patients with smaller AAA, and there remains no conclusive evidence to justify a reduction in guidelines for treatment threshold. Large registry analyses have demonstrated greater operative morbidity with very large (>6.0 cm) AAAs, 15 but no benefit from treating if <5.5 cm in diameter. A recent cost-effectiveness simulation analysis by Tomee et al found that reduction of the treatment threshold to 5.0 cm could result in significantly more surgical procedures, including re-interventions and subsequent operative mortality, at the cost of an estimated US$1 million per rupture-related death prevented.…”
Section: Objectivesmentioning
confidence: 99%